Author Correction: Assessing animal affect: an automated and self-initiated judgement bias task based on natural investigative behaviour. Issue 1 (December 2018) - Jones, Samantha; Neville, Vikki; Higgs, Laura; Paul, Elizabeth; Dayan, Peter; Robinson, Emma; Mendl, Michael
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.